Capture the flag: computer science style - Robertson, Kathy Lynn, author; Massey, Dan, author; Ray, Indrajit, author (Colorado State University. Libraries, 2006)
With today's technology, and corresponding security vulnerabilities it is important for students to have security in the forefront of their thought process when creating or maintaining networks, hardware and software. It was for this reason that Capture the Flag: Computer Science Style event was planned. Starting with a certain set of widely known security exploits, each team was to hack, crack and sneak into servers, steal password, sniff traffic and take advantage of certain security exploits. This poster will cover one of these security hacks in detail, and explain the goals and results from the first ever Capture the Flag: Computer Science Style event.
Keywords: Computer networks -- Security measures